Dynamic and control of fuel cell system - Younis, M.A.A.; Rahim, N.A.; Mekhilef, Saad (2008)
In this paper, dynamic simulation of a fuel cell system studied using MATLAB/SIMULINK. The paper presents the dynamic model of Proton Exchange Membrane Fuel Cell (PEMFC). The fuel cell output voltage is proportional to the change of the current drawn from the fuel cell model. Phase control full bridge dc/dc converter considered to match the unregulated voltage produced by the fuel cell model to the needed application voltage. PID controller has been selected to regulate the fuel cell output voltage. PWM-based inverter serves as the interface between the dc/dc converter and the ac load. Three-phase inverter used to drive three phase load. Third Harmonic Injection Pulse Width Modulation used to drive the three-phase inverter so that minimum harmonic distortion and maximum usage of the fuel cell voltage on the three-phase inverter output. Simulation results provided to validate the design.